Expression of TSLP and Downstream Molecules IL-4, IL-5, and IL-13 on the Eye Surface of Patients with Various Types of Allergic Conjunctivitis - Xiaofen Zheng; Juan Yao; Bing Li (Journal of Ophthalmology)
Background. The pathogenesis of allergic conjunctivitis has not been clearly established. Moreover, previous studies fail to consider human models of allergic conjunctivitis. This study investigated the expression of thymic stromal lymphopoiet in TSLP and its downstream molecules in conjunctival scrappings and tear. Methods. This cross-sectional study compares patients with vernal keratoconjunctivitis (VKC), seasonal allergic conjunctivitis (SAC), and perennial allergic conjunctivitis (PAC) with normal controls. There are 80 people recorded in Shanxi Eye Hospital. Increasingly, 20 are with VKC, 20 are with SAC, 20 are with PAC, and the remaining 20 are normal controls. Conjunctiva were harvested for total RNA extraction and gene expression by real-time polymerase chain reaction. Epithelial cells were collected to make pathological sections for immunohistochemical staining. Human tears were evaluated by Luminex microbead assay. A P value less than 0.05 from Dunnett’s post hoc test in SPSS means a statistical significant distinction. Results. Positive expression in conjunctival cells of patients with allergic conjunctivitis. The expression of TSLP and IL-4, IL-5, and IL-13 mRNA shows a statistically significant difference (P<0.05). TSLP and IL-4, IL-5, and IL-13 concentrations show a statistically significant difference (P<0.01). Conclusions. This study suggests that TSLP and downstream molecules are expressed in patients with various types of allergic conjunctivitis.